2020
DOI: 10.2478/helm-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Dirofilaria immitis in Bulgaria: the first genetic baseline data and an overview of the current status

Abstract: SummaryDirofilaria immitis, the agent of canine dirofilariosis, is a common parasite of domestic and wild carnivores with zoonotic potential and worldwide distribution, being endemic in many countries. Bulgaria is among European countries recognized as endemic for this heartworm parasite. In the present study, D. immitis adults recovered from pulmonary arteries of domestic dog and golden jackal originating from the Pazardzhik region in southern Bulgaria, and from red fox originating from the Plovdiv region in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…In Europe, infection with Dirofilaria spp. in dogs was identified in many countries including Austria [12], the Baltic countries [23], Bulgaria [24], the Czech Republic and Slovakia [25], France [26], Greece [6,27], Hungary [28], Italy [29][30][31], Serbia [32], and Spain [33], with minor differences among reports [13]. An up-to-date and accurate picture of Dirofilaria infections in central and northern European countries is provided by a study by Fuehrer et al, 2021, which states that, although the number of studies has increased in recent years, epizootiological knowledge is fragmented [34].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, infection with Dirofilaria spp. in dogs was identified in many countries including Austria [12], the Baltic countries [23], Bulgaria [24], the Czech Republic and Slovakia [25], France [26], Greece [6,27], Hungary [28], Italy [29][30][31], Serbia [32], and Spain [33], with minor differences among reports [13]. An up-to-date and accurate picture of Dirofilaria infections in central and northern European countries is provided by a study by Fuehrer et al, 2021, which states that, although the number of studies has increased in recent years, epizootiological knowledge is fragmented [34].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported prevalence between 16.2 and 34.3% in the central-southern region (Stara Zagora) [85,86]. In the city of Sofia (western), the prevalence ranged between 4.8 and 25.8%, while the prevalence rose to 34.7% in the Sofia region [81,83,[86][87][88]. In addition, Iliev et al [80] showed a prevalence of 11.3% in the south and 8.3% in the north, with a mean prevalence of 10.5%.…”
Section: Endemic Areas (■) and Sporadic Cases Reported (■) )mentioning
confidence: 95%
“…In Bulgaria, recent studies reported prevalence between 4.8-34.7%, being higher in the central, eastern, and southern regions and lower in the western and south-western regions [80][81][82]. In the central southern region, prevalence between 15.74 and 17.8% were reported, while prevalence in the south-western region was 5.5% [83,84]. Other studies have reported prevalence between 16.2 and 34.3% in the central-southern region (Stara Zagora) [85,86].…”
Section: Endemic Areas (■) and Sporadic Cases Reported (■) )mentioning
confidence: 96%
See 1 more Smart Citation
“…For D. immitis , a trend to spread in north-eastern Europe has been observed in recent decades (Genchi et al 2011 ). The northern border of transmission of D. immitis is not well documented to date, but cases have been identified as north as Central France, Southern Switzerland, Northern Italy, Slovakia, Bulgaria, Hungary and Ukraine (Deplazes et al 1995 ; Farkas et al 2020 ; Hermosilla et al 2006 ; Laidoudi et al 2019 ; Mendoza-Roldan et al 2020 ; Panayotova-Pencheva et al 2020 ; Petruschke et al 2001 ; Sassnau et al 2014a ; Széll et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%